2016
DOI: 10.1007/s00259-016-3486-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and predictive value of sstr2-immunohistochemistry and sstr2-targeted imaging in neuroendocrine tumors

Abstract: Our results suggest sstr as an independent prognostic marker in NETs. Sstr-immunohistochemistry correlates with sstr-imaging; however, sstr-imaging is more accurate for determining the individual prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 15 publications
8
42
0
Order By: Relevance
“…SSTR2 expression was determined in corresponding samples. In concordance with other studies we found varying SSTR2 expression in tumour lesions among SI-NET patients [3]. SSTR2 expression did not differ solely based on tumour location.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SSTR2 expression was determined in corresponding samples. In concordance with other studies we found varying SSTR2 expression in tumour lesions among SI-NET patients [3]. SSTR2 expression did not differ solely based on tumour location.…”
Section: Discussionsupporting
confidence: 92%
“…A high uptake on 68 Ga-DOTATATE PET has been reported to predict treatment response [13]. Some studies suggest a correlation between immunohistochemically (IHC) quantified SSTR2 expression in tissue samples and uptake in SSTR imaging with 68 Ga-DOTATATE-PET or 111 In-octreotide scintigraphy [3,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…The association of some parameters in this dataset with PFS and OS has already been described in other papers (12,23,25,(28)(29)(30)32,35,36). However, to our knowledge, this is the first study that combines all parameters in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%
“…Brunner et al found that SSTR type 2 expression is an independent prognostic marker for OS in 279 NET patients. A subgroup analysis of 61 patients with pancreas NET (pNET) showed that SSTR expression is not a prognostic marker for OS in pNET (12). Other nonhistologic parameters associated with survival after PRRT include gene cluster expression (13), primary tumor site (14), resection of the primary tumor (15), dominant liver metastases, and lesion size (14).…”
mentioning
confidence: 99%
“…As a feature of differentiation, SSTR expression may be complementary to pathology in differentiating well- from poorly differentiated grade 3 NEN. Recent evidence suggests that SSTR PET imaging results are highly correlated with SSTR-2 expression on immunohistochemistry but more accurate for predicting individual prognosis [70]. …”
Section: Prrt Requirementsmentioning
confidence: 99%